Soil stabilization using chemical additive - Muhammad Audi Adib, Mohd Zim (2015)
Subgrade is a base layer that is crucial in constructing road that act as a medium in order to cater all the load from the traffic and the load of the road itself. The thickness of the constructing road, stability, strength and the cost of road construction eventually will depend on the strength of subgrade. In other point of view, the soil subgrade will also influence the life expectancy of the road. Soil stabilization is a method to cover the weakness of soil. In this study, soil sample is taken at Kompleks Sawit Sri Meranti, Lepar. The objective of the research is to determine the soil characteristic of untreated soil used in this study, to evaluate the existing strength of treated soil with bi-sulphate at site and to determine the strength of soil when freshly treated with bi-sulphate. Chemical additives using bi-sulphate is another option of soil stabilization that is to study the effect of the usage of these chemical to clay type soil on subgrade layer. The study was conducted by adding different quantity of chemical which is 3, 9 and 15 %. Soil sample was cured for 7, 14 and 28 days for unconfined compression test (UCT). The soil characteristics was defined by having plastic index of 28.69 %, specific gravity value of 2.51, optimum moisture content of 30 % and maximum dry density of 1.37 g/cm3. The test conducted was California Bearing Ratio (CBR) and unconfined compression test which was conducted to determine the soil bearing capacity and strength of soil. The maximum strength for existing treated soil with bi-sulphate at site was 1178.83 kN/m2 while for untreated sample was 612.52 kN/m2. When soil was added with 3 % of bi-sulphate, maximum strength of each curing days were 725.68 kN/m2, 742.59 kN/m2 and 800.92 kN/m2 respectively. For 9 % of bi-sulphate added, the soil strength were 893.66 kN/m2, 968.86 kN/m2 and 993.13 kN/m2 respectively for each curing days. Lastly, when 15 % of bi-sulphate added, the soil strength were 812.49 kN/m2, 867.10 kN/m2 and 905.10 kN/m2 respectively. While for CBR when 3, 9 and 15 % of bi-sulphate added were 7.81, 8.18 and 8.22 respectively. For CBR value for untreated and existing treated soil with bi- sulphate at site are 4.68 and 8.4 respectively. Based on the result, it shows that bi-sulphate was capable in increasing the strength of soil. The maximum soil strength was gained when the soil is mixed at 9% with the chemical. The existing strength of treated soil with bi-sulphate at site shows that it has higher strength compared to freshly treated soil.